The Effect of Ionizing Radiation on Workers in Baghdad Hospital for Radiotherapy and Nuclear Medicine - A. Jawad, Asmaa; S. Zageer, Dheaa (Al-Nahrain Journal of Science, 2025)
This work involves the investigation of the effect of ionizing radiation on hospital workers to estimate the risks they are exposed to during their daily working hours and for many years, and to take the necessary precautions to ensure the occupational safety of this category of workers. Blood samples were collected from Baghdad Hospital for Nuclear Medicine in the Medical City in Iraq. Some parameters were studied clinically using specific kits, including liver enzymes ALT, AST, ALP, vitamin D3, S-Firrtin, and urea, under a P value less than 0.05. The results showed that all parameters did not change (not significant) in this study, except for urea, which was significant. In conclusion, urea can be used as a biomarker to determine the effect of low-dose ionizing radiation on healthcare workers.